Affordable optical clearing and immunolabelling in mouse brain slices - Phillip M. Muza; Marta Pérez; Suzanna Noy; Miyu Kurosawa; Loukia Katsouri; Victor L. J. Tybulewicz; Elizabeth M.C. Fisher; Steven J. West (BMC Research Notes, 2023)
Abstract Traditional histological analysis is conducted on thin tissue sections, limiting the data capture from large tissue volumes to 2D profiles, and requiring stereological methods for 3D assessment. Recent advances in microscopical and tissue clearing methods have facilitated 3D reconstructions of tissue structure. However, staining of large tissue blocks remains a challenge, often requiring specialised and expensive equipment to clear and immunolabel tissue. Here, we present the Affordable Brain Slice Optical Clearing (ABSOC) method: a modified iDISCO protocol which enables clearing and immunolabeling of mouse brain slices up to 1 mm thick using inexpensive reagents and equipment, with no intensive expert training required. We illustrate the use of ABSOC in 1 mm C57BL/6J mouse coronal brain slices sectioned through the dorsal hippocampus and immunolabelled with an anti-calretinin antibody. The ABSOC method can be readily used for histological studies of mouse brain in order to move from the use of very thin tissue sections to large volumes of tissue – giving more representative analysis of biological samples, without the need for sampling of small regions only.